Optimizing User Interface of MBKM Information System & Academic Services using Design Thinking Method (Case Study: Tadulako University) - Reinaldy Mansa, Jeremy; Anggun Pratama, Septiano; Wirdayanti, Wirdayanti; Angreni, Dwi Shinta (Pandawan Sejahtera Indonesia, 2024)
This study addresses the usability challenges faced by Tadulako University's MBKM & Academic Services Information System (SITAMPAN), developed in response to the Ministry of Education’s Merdeka Belajar - Kampus Merdeka (MBKM) initiative. By applying a structured Design Thinking approach, this research seeks to present a novel solution for enhancing user experience and system usability in educational information systems. Through the System Usability Scale (SUS) and User Experience Questionnaire (UEQ) evaluations, initial findings indicated a low usability score (SUS: 41.75, grade